Concerning the issue of early diagnostics of low tannin content in faba bean seeds (Vicia faba L.) - S. M. Mamedova; V. S. Popov; A. E. Solovyeva; I. N. Perchuk; L. L. Malyshev; M. A. Vishnyakova (Труды по прикладной ботанике, генетике и селекции)
Background. The use of faba bean (Vicia faba L.) as a feed and food plant is hindered by the presence of antinutritional substances and in particular phenolic compounds – tannins – in the seed coat. The existence of low-tannin or zero-tannin forms in the faba bean gene pool allows breeders to promote this trait. The aim of this work was to carry out biochemical validation of a known morphological marker of low tannin content and identify relationships of some phenotypic traits characterized by accumulation of phenolic compounds (tannins and anthocyanins) with their concentration for use as additional morphological markers of the low content of these antinutrients in bean seeds.Materials and methods. Associations of the presence/absence of anthocyanin in seedlings, pigmentation on petals, and dark extrafloral nectaries on stipules with the content of tannins and anthocyanins were analyzed in 10 faba bean accessions with different seed coat colors from the VIR collection. The plants were grown and evaluated in Leningrad Province in 2020–2021. Tannins in seeds were assessed using Leventhal’s method. Anthocyanins were analyzed in the green biomass of plants using a spectrophotometric method.Results and conclusion. Different combinations of the studied morphological features associated with the coloration of the studied organs were found. A high positive correlation between the levels of anthocyanins and tannins (r = 0.79) was identified as well as a direct connection of the high value of these traits with the presence of a dark extrafloral nectary on stipules and anthocyanin in seedlings. The absence of anthocyanin staining on seedlings and the absence of dark-colored extrafloral nectaries on stipules can serve as markers of low-tannin genotypes in the early stages of plant development. The light seed coat color that does not darken for a long time may also be the evidence of low tannin content.